Factor associated with Stunting Incidents in Kepyar Village, Purwantoro District, Wonogiri Regency in 2021: Faktor yang berhubungan dengan Kejadian Stunting di Desa Kepyar Kecamatan Purwantoro Kabupaten Wonogiri Tahun 2021 - Susi Shorayasari; Andini Kurnia Wati; Dieta Nurrika (Amerta Nutrition, 2022)
Background: The WHO-MGRS (Multicenter Growth Reference Study) recommendations based on the height for age index define stunting as a condition in which the body is short or extremely short. The incidence of stunting among children under five is predicted to reach 21.9% in 2020 by the World Health Organization (WHO). Stunting affects 149.0 million children, who run the risk of developing stunted growth, poor brain development, lower IQ, and disease vulnerability. Objectives: The study aimed to find out the variables associated with the incidence of stunting in 2021 in Kepyar Village, Purwantoro District, Wonogiri Regency. Methods: The research design was case-control with a ratio of 1:1 consisting of 22 samples from cases and 22 samples from controls. 22 individuals who were not deemed to be at risk of suffering stunting made up the control sample for toddlers. Between November 2021 and January 2022, the study was carried out. Low birth weight (LBW), birth length, exclusive breastfeeding, mother's last educational level, mother's height, socioeconomic status, accessibility to weaning food, early breastfeeding initiation, and also considered the mother's age at conception were all independent variables.  The dependent variable is stunting, which can be either chronic or mild to severe (-2 SD). Fisher's Exact Test was used to analyze this study. Results: The majority of children were not LBW (90.9%), followed by normal birth length (81.8%), exclusive breastfeeding (56.8%), low education level of the mother (72.7%), mother's height was not at risk (72.7%), early breastfeeding initiation (63.6%), low socioeconomic status (63.6%), proper weaning food (77.3%), and maternal age during pregnancy is not at risk (54.5%). Early initiation of breastfeeding and stunting incidents showed a statistically significant association (p-value of 0.005), then there was also a relationship between socioeconomic status and stunting incidents (p-value of 0.028). Conclusions: Socioeconomic status and early initiation of breastfeeding are associated with stunting incidents. To lower the frequency of stunting in Kepyar Village, early initiation of breastfeeding promotion needs to be optimized.